Psychological Capital Analysis in Assessing the Career Feasibility of Vocational Graduates as Human Resource Suppliers in the Electronics Industry - Wikansari, Rinandita; Wiyono, Adrianto Sugiarto; Subekti (ADMAN: Journal of Contemporary Administration and Management, 2023)
The rapid growth of the electronics industry in the era of globalization demands the availability of high-quality Human Resources (HR) ready to compete in the job market. Graduates from vocational programs, with a focus on technical skills, play a vital role in supplying the workforce needs in this industry. However, the success of vocational graduates' careers is not solely determined by technical competence. This research aims to analyze psychological capital in assessing the career feasibility of vocational graduates as human resource suppliers in the electronics industry. The approach encompasses an in-depth examination of relevant literature employing qualitative analysis, aiming to gain a comprehensive insight into the topic from 2004 to 2023. The study results indicate that in assessing the career feasibility of vocational graduates as human resource suppliers in the electronics industry, it is essential to emphasize that interpersonal skills, autonomy, self-motivation, emotional intelligence, and leadership abilities play a crucial role. The dynamic electronics industry requires individuals with strong technical skills as well as the ability to adapt, collaborate within teams, and possess good emotional intelligence. Therefore, it is crucial not to solely assess technical qualifications when evaluating vocational graduates. Vocational education should pay more attention to the early development of psychological skills so that graduates are prepared to face various challenges in the ever-evolving professional world.